2013
DOI: 10.2174/1874434601307010107
|View full text |Cite
|
Sign up to set email alerts
|

Meanings Over Time of Working as a Nurse in Elderly Care

Abstract: Abstract:Background: Although registered nurses (RNs) play a central role in the care of older persons, their work in elderly care has historically been described as "low status" in nursing. This is especially problematic due to the global issue of RN turnover, but there is still little evidence of how to change this trend. Better understanding is needed of the reasons why RNs work in elderly care, as well as knowledge of whether these reasons have changed over time. Aim:The aim was to explore the meaning of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In this study, we learned from NAs’ experiences and knowledge of how a meaningful daily life can be developed for older persons in a nursing home. For a well-functioning team [ 6 , 12 , 13 ] it is crucial to learn from NAs and use that knowledge in the care of older persons, that is to sense and find the right way of being, and read the older person to judge how the person is feeling. It is crucial to adapt to the older person and share their daily life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we learned from NAs’ experiences and knowledge of how a meaningful daily life can be developed for older persons in a nursing home. For a well-functioning team [ 6 , 12 , 13 ] it is crucial to learn from NAs and use that knowledge in the care of older persons, that is to sense and find the right way of being, and read the older person to judge how the person is feeling. It is crucial to adapt to the older person and share their daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Blomberg et al .’s [6] study showed that the team can design this care and they can initiate changes in the care. A well-functioning team is crucial to good quality of care [13] because the better they work as a team the better everyone feels, including the older persons [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This interaction seemed to be important source of meaning in caregivers' work, since caregivers expressed a lack of being appreciated by their employers, the care receivers' next-of-kin and society. The caregivers' wish of being present and having disturbance-free interactions can be understood in relation to the concept of attentiveness 5 and has likewise been described in a study 36 where RNs in care for older people valued caring time instead of administrative tasks. Caregivers in our study wanted to see the person behind the illness and be attentive towards not only the person's medical conditions but also their personal preferences and shifting needs.…”
Section: Discussionmentioning
confidence: 99%